Factors Affecting the Use of Online Applications for Business Process Reengineering (BPR) Acceleration in Micro, Small and Medium Enterprises (MSMEs) as a Consequence of Covid-19 Pandemic - Purnamasari, Dian Indri (Archives of Business Research, 2020)
The aim of this research is testing the factors that affect the use of online applications for the acceleration of Business Process Reengineering (BPR) system in Micro, Small, and Medium Enterprises during Covid-19 pandemic will be the next question. This study used primary data from a web-based survey—Google Form—to keep up with current technology and to comply with COVID-19 Social Distancing protocol and to stay alert. We make observation of MSMEs was conducted in Yogyakarta. The results of analysis presented earlier have led us to conclude that (1) personal factors do not affect the use of online application, (2) organizational factors do not affect the use of online application, (3) online application success affects the use of online application, and (4) emotional Reaction affects the use of online application.